2016
DOI: 10.1002/stem.2257
|View full text |Cite
|
Sign up to set email alerts
|

LIM Homeobox Domain 2 Is Required for Corneal Epithelial Homeostasis

Abstract: The cornea requires constant epithelial renewal to maintain clarity for appropriate vision. A subset of stem cells residing at the limbus is primarily responsible for maintaining corneal epithelium homeostasis. Trauma and disease may lead to stem cell deficiency and therapeutic targeting to replenish the stemness capacity has been stalled by the lack of reliable corneal epithelial stem cell markers. Here we identified the location of Lhx2 in mice (mLhx2) cornea and conjunctival tissue using an Lhx2eGFP reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…In the current study, miR-506 was suggested to be involved in inhibiting the activation of the Wnt/β-catenin signaling pathway by down-regulating LHX4, by means of which the EMT-related signals were inhibited. It has been suggested that LHX2 plays a pivotal role in various epithelial-mesenchymal interactions [49]. Multiple signaling pathways, including the nuclear factor kappa B, EGFR, Wnt and transforming growth factor-β (TGF-β) signaling pathways, are involved in the regulation of EMT and LNM [5053].…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, miR-506 was suggested to be involved in inhibiting the activation of the Wnt/β-catenin signaling pathway by down-regulating LHX4, by means of which the EMT-related signals were inhibited. It has been suggested that LHX2 plays a pivotal role in various epithelial-mesenchymal interactions [49]. Multiple signaling pathways, including the nuclear factor kappa B, EGFR, Wnt and transforming growth factor-β (TGF-β) signaling pathways, are involved in the regulation of EMT and LNM [5053].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that both central and limbal epithelial cells are responsive to ocular surface injury, possibly exerting different roles in the process of wound healing. After scraping the epithelium, the cornea healed fully within 72 hours, as reported earlier [38], but we could not detect a change in the Bmi1 + cell progeny patterning nor the amount or distribution of the Ki67+ cells. Instead, we saw that the epithelium was thin 18 hours after injury, which corresponds to the active period of healing.…”
Section: Discussionsupporting
confidence: 80%
“…As LESCs are induced to proliferate in order to repair large wounds ( Lehrer et al., 1998 ), the poor wound healing response suggests LESCs are deficient in Lrig1 −/− mice. Similar evidence suggests that the abnormal corneal epithelial morphology, implying impaired corneal homeostasis, which was seen in some K14-Cre ; Lhx2 fl/fl mice also involved a LESC deficiency ( Sartaj et al., 2016 ). After successive corneal epithelial debridements, wound healing was incomplete in K14-Cre ; Lhx2 fl/fl mice and their corneal epithelium contained goblet cells and K15-positive cells.…”
Section: Introductionmentioning
confidence: 68%